2010
DOI: 10.1111/j.1939-165x.2010.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous embryonal rhabdomyosarcoma in a dog: cytologic, immunocytochemical, histologic, and ultrastructural features

Abstract: A subcutaneous mass on the left antebrachium of an 11-year-old intact female English Pointer dog was evaluated presurgically by cytologic examination and immunocytochemical staining. The sample consisted of discrete, variably sized, markedly pleomorphic neoplastic cells that expressed vimentin with diffuse cytoplasmic staining, desmin with focal paranuclear staining, and myoglobin with diffuse cytoplasmic staining, consistent with a diagnosis of rhabdomyosarcoma. Lymphocytic and histiocytic markers were negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…The round cell variant of embryonal rhabdomyosarcoma was considered due to the large cellular diameters. However, the scant cytoplasm made this diagnosis less likely, as cytologic features typical of rhabdomyoblasts, including abundant basophilic cytoplasm, and frequent paranuclear clear halos, were absent in the present case. Cellular cannibalism, occasionally observed in this neoplasm (Figure B), has been suggested as a diagnostic marker of malignancy, although it is not specific for NEC …”
Section: Discussioncontrasting
confidence: 54%
“…The round cell variant of embryonal rhabdomyosarcoma was considered due to the large cellular diameters. However, the scant cytoplasm made this diagnosis less likely, as cytologic features typical of rhabdomyoblasts, including abundant basophilic cytoplasm, and frequent paranuclear clear halos, were absent in the present case. Cellular cannibalism, occasionally observed in this neoplasm (Figure B), has been suggested as a diagnostic marker of malignancy, although it is not specific for NEC …”
Section: Discussioncontrasting
confidence: 54%
“…Extensive metastases of rhabdomyosarcomas originating in the urinary bladder have been reported; however, additional imaging was not performed on this patient to confirm or rule out this possibility. A subcutaneous embryonal rhabdomyosarcoma has been reported with metastasis to a lymph node, and metastasis to the lymph node from the dermal mass was considered to be most likely in this case.…”
Section: Discussionmentioning
confidence: 76%
“…Allows for the use of antibodies that are not effective in formalin fixed tissue, for example, T‐cell subsets Can offer rapid pre‐surgical diagnosis to aid in surgical planning and chemotherapeutic protocols Unlike flow cytometry, ICC allows assessment of cell morphology and direct visualization of the cell population of interest and its immunoreactivity.…”
Section: Resultsmentioning
confidence: 99%
“…A common mistake in the application of ICC is ordering too few stains, which either produces bias towards the favoured diagnosis or results in the lack of a definitive diagnosis. The importance of this was stressed by Fowler et al in a review of ICC in human medicine and was demonstrated in a case report of rhabdomyosarcoma in a dog . In this case report, the authors proposed a list of differential diagnoses which included rhabdomyosarcoma along with a tumour of histiocytic or plasma cell origin, based on cytological evaluation of a subcutaneous tumour.…”
Section: Discussionmentioning
confidence: 99%